Reliability of Motor Evoked Potentials Induced by Transcranial Magnetic Stimulation: The Effects of Initial Motor Evoked Potentials Removal - Hashemirad, Fahimeh (Basic Clin Neurosci, 2017)
INTRODUCTION: Transcranial magnetic stimulation (TMS) is a useful tool for assessment of corticospinal excitability (CSE) changes in both healthy individuals and patients with brain disorders. The usefulness of TMS-elicited motor evoked potentials (MEPs) for the assessment of CSE in a clinical context depends on their intra-and inter-session reliability. This study aimed to evaluate if removal of initial MEPs elicited by using two types of TMS techniques influences the reliability scores and whether this effect is different in blocks with variable number of MEPs. METHODS: Twenty-three healthy participants were recruited in this study. The stimulus intensity was set at 120% of resting motor threshold (RMT) for one group while the stimulus intensity was adjusted to record MEPs up to 1 mV for the other group. Twenty MEPs were recorded at 3 time points on 2 separate days. An intra-class correlation coefficient (ICC) reliability with absolute agreement and analysis of variance model were used to assess reliability of the MEP amplitudes for blocks with variable number of MEPs. RESULTS: A decrease in ICC values was observed with removal of 3 or 5 MEPs in both techniques when compared to all MEP responses in any given block. Therefore, removal of the first 3 or 5 MEPs failed to further increase the reliability of MEP responses. CONCLUSION: Our findings revealed that a greater number of trials involving averaged MEPs can influence TMS reliability more than removal of the first trials.